2022
DOI: 10.1038/s41598-022-24192-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and clinical outcome after radiotherapy of patients with intracranial meningioma

Abstract: This retrospective, single-institutional study investigated long-term outcome, toxicity and health-related quality of life (HRQoL) in meningioma patients after radiotherapy. We analyzed the data of 119 patients who received radiotherapy at our department from 1997 to 2014 for intracranial WHO grade I-III meningioma. Fractionated stereotactic radiotherapy (FSRT), intensity modulated radiotherapy (IMRT) or radiosurgery radiation was applied. The EORTC QLQ-C30 and QLQ-BN20 questionnaires were completed for assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…There are some other papers assessing the QoL utilizing the QLQ-C30 and QLQ-BN20 questionnaires of intracranial meningioma patients treated with photon radiotherapy. One very recent publication sent out these questionnaires a median of 4.8 years after treatment to the patients with a good response rate of almost 60% [ 55 ]. The authors reported a lowered QoL and attributed it to the radiotherapy, but due to the retrospective nature of this investigation, no baseline values were available and thus no conclusive statement can be made.…”
Section: Discussionmentioning
confidence: 99%
“…There are some other papers assessing the QoL utilizing the QLQ-C30 and QLQ-BN20 questionnaires of intracranial meningioma patients treated with photon radiotherapy. One very recent publication sent out these questionnaires a median of 4.8 years after treatment to the patients with a good response rate of almost 60% [ 55 ]. The authors reported a lowered QoL and attributed it to the radiotherapy, but due to the retrospective nature of this investigation, no baseline values were available and thus no conclusive statement can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Overall QoL in meningioma patients treated with radiotherapy may be lower than in those treated with surgery. 93 Specifically, in a study of 118 patients with NF2, patients whose treatment included any form of radiotherapy had a worse QoL than patients who did not, 94 although it is worth considering that the need for radiotherapy may have been due to a more aggressive disease course, also predictive of a worse QoL. 95 …”
Section: Clinical Management and Quality Of Life Outcomesmentioning
confidence: 99%
“…This was attributed to the new onset of postoperative deficits including hemiparesis, swallowing difficulties, and hypoacusis. Intraoperative electrophysiological monitoring and adjuvant therapies such as radiation and systemic therapies may improve HRQoL outcomes in this population [20,61,62]. As a result, NTR may lead to better QOL outcomes than GTR for PCM patients.…”
Section: Posterior Skull Base Meningiomasmentioning
confidence: 99%